Bioactive Materials Subjected to Erosion/Abrasion and Their Influence on Dental Tissues - Viana, I. E. L.; Alania, Y.; Feitosa, S.; Borges, A. B. [UNESP]; Braga, R. R.; Scaramucci, T. (Operative Dentistry Inc, 2020)
Objective: The objective of this study was to evaluate the effect of erosion or erosion-abrasion on bioactive materials and adjacent enamel/dentin areas. Methods and Materials: Enamel and dentin blocks (4x4x2 mm) were embedded side by side in acrylic resin, and a standardized cavity (1.2x4x1.5 mm) was prepared between them. Preparations were restored with the following materials: composite resin (Filtek Z350, control); experimental composite containing dicalcium phosphate dihydrate particles (DCPD); Giomer (Beautifil II), high viscosity glass ionomer cement (GIC, Fuji IX); and a resin-modified GIC (Fuji II LC). The specimens were submitted to two cycling models (n=10): erosion or erosion-abrasion. The challenges consisted of five-minute immersion in 0.3% citric acid solution, followed by 60-minute exposure to artificial saliva. Toothbrushing was carried out twice daily, 30 minutes after the first and last exposures to acid. Dental and material surface loss (SL, in mu m) were determined by optical profilometry. Data were analyzed with Kruskal-Wallis and Dunn tests (alpha=0.05). Results: Under erosion, for enamel, only the GIC groups presented lower SL values than Z350 (p<0.001 for Fuji IX and p=0.018 for Fuji II LC). For dentin, none of the materials showed significantly lower SL values than Z350 (p>0.05). For material, the GICs had significantly higher SL values than those of Z350 (p<0.001 for Fuji IX and p=0.002 for Fuji II LC). Under erosion-abrasion, the enamel SL value was significantly lower around Fuji II LC compared with the other materials (p<0.05). No significant differences were observed among groups for dentin SL (p=0.063). The GICs and Giomer showed higher SL values than Z350 (p<0.001 for the GICs and p=0.041 for Giomer). Conclusion: Both GIC-based materials were susceptible to erosive wear; however, they promoted the lowest erosive loss of adjacent enamel. Against erosion-abrasion, only Fuji II LC was able to reduce enamel loss. For dentin, none of the materials exhibited a significant protective effect.